A two-year retrospective study on hepatitis b cases in Hospital Universiti Sains Malaysia (HUSM) from 2018-2019 - Sang, Chong Yuen (2020)
Hepatitis B virus (HBV) infection is a deadly infectious disease worldwide. HBV infection is predominantly high in endemic region which includes Southeast Asia (SEA). Malaysia is one of the endemic country in SEA and has higher incidences of hepatitis B (HB) infection. Given that, there is a paucity of information on epidemiological trend and patient clinical data, therefore the goal of this project is to analyze HB cases reported to Hospital USM, Kubang Kerian, Kelantan. Although data was collected from a single hospital, the catchment area of this hospital is large as most patients from Kelantan state are referred or walk in into this hospital for diagnosis and treatment. Data were extracted from the hospital information system and exported into Microsoft excel and were analysed using SPSS software version 26. There are total 232 HB patients are newly diagnosed and on-going follow up in Hospital USM from 2018 until 2019 were the subjects of this research study. Of that, 65% of HB patients were males and most patients were in the economically productive age group between 30 to 60 years old. Regarding ethnicity, most of the patients are Malays followed by Chinese and Indians. Besides that, majority of the HB patients were non-healthcare workers and retired group. The clinical data of HB indicated more patients were chronically infected with HB than acute. The common treatment that were administered to chronic HB patients are antiviral drugs (AVT) and interferons (IFN). Both are standard of care treatment for chronic hepatitis B (CHB) infection. Nevertheless, the univariate analyses were included in this research study. From the analyses, we manage to establish an association between age and other sociodemographics distributions only for HB patient gender, phase of infection and complication of HB infection. The risk factors of HB infection included in this study were age, gender and ethnicity. The results shown that, there is not statistically significance in these risk factors. Given the data obtained in this study were secondary data, some of the data are not available and might not be updated from time to time. Thus, it is not comprehensive enough to reflect the prevalence of hepatitis B cases in Malaysia. On-going study is crucial to overcome the limitation in this project and establish of the epidemiological data of hepatitis B infection would be important for public health information.